Pengaruh Edukasi Kesehatan Terhadap Kesiapsiagaan Masyarakat Dalam Pertolongan Pertama Hipoglikemia: The Effect of Health Education on Community Preparedness in Providing First Aid for Hypoglycemia - Ariani, Sri Purwanti; Indrayadi, Indrayadi; Yuhansyah, Yuhansyah; Ernawati, Ernawati; Rapika, Rapika (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Hypoglycemia is an emergency condition in individuals with diabetes mellitus that can lead to decreased consciousness and even death if not managed promptly and appropriately. A low level of community knowledge and preparedness in recognizing the signs and symptoms and in providing first aid for hypoglycemia constitutes a major risk factor for the development of complications. This activity aimed to improve the preparedness of the Basirih Village community in providing first aid for hypoglycemic events through health education. This activity employed a pre-experimental design with a one-group pretest–posttest approach involving an intervention group and a control group. The sample consisted of residents of Basirih Village selected using purposive sampling. The measured variable was community preparedness in hypoglycemia first aid, encompassing knowledge, attitudes, and skills. The research instruments included standardized questionnaires and skill observation checklists. Data analysis was conducted by comparing pretest and posttest scores in both groups. The results demonstrated a significant increase in knowledge, attitudes, skills, and overall preparedness scores in the intervention group after the provision of health education (p < 0.001). In contrast, no significant differences were observed between pretest and posttest scores in the control group (p > 0.05). These findings indicate that health education has a significant effect on improving community preparedness in providing first aid for hypoglycemia. It can be concluded that health education is effective in enhancing the preparedness of the Basirih Village community toward hypoglycemic events. This activity is recommended to be implemented continuously as a promotive and preventive effort to reduce hypoglycemia-related complications at the community level.